2000
DOI: 10.1146/annurev.neuro.23.1.155
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Circuits in the Brain

Abstract: The field of neuroscience has, after a long period of looking the other way, again embraced emotion as an important research area. Much of the progress has come from studies of fear, and especially fear conditioning. This work has pinpointed the amygdala as an important component of the system involved in the acquisition, storage, and expression of fear memory and has elucidated in detail how stimuli enter, travel through, and exit the amygdala. Some progress has also been made in understanding the cellular an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

186
4,481
8
145

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 7,177 publications
(4,820 citation statements)
references
References 120 publications
186
4,481
8
145
Order By: Relevance
“…emotional dysregulation) is associated with a number of psychopathologies (Davidson, 1998(Davidson, , 2002Phillips, Ladouceur, & Drevets, 2008a, 2008b. Despite the importance of this ability, most studies of emotion-related responses focus on the perception and classification of emotional stimuli, rather than the regulation involved in the preparation to complete an appropriate regulated action (Burgdorf & Panksepp, 2006;Calder, Lawrence, & Young, 2001;LeDoux, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…emotional dysregulation) is associated with a number of psychopathologies (Davidson, 1998(Davidson, , 2002Phillips, Ladouceur, & Drevets, 2008a, 2008b. Despite the importance of this ability, most studies of emotion-related responses focus on the perception and classification of emotional stimuli, rather than the regulation involved in the preparation to complete an appropriate regulated action (Burgdorf & Panksepp, 2006;Calder, Lawrence, & Young, 2001;LeDoux, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Although much evidence indicates that the amygdala is a critical site of plasticity for the acquisition of classically conditioned fear responses (16), the effects of the manipulations mentioned above seem to result from alterations of memory storage in other neuronal structures (8). For instance, it was shown that immediate postlearning injection of amphetamines in the BLA increases hippocampal-dependent storage of spatial information and striatal-dependent storage of response information.…”
mentioning
confidence: 99%
“…We used an aversive loud sound as the unconditioned stimulus (Morris & Dolan 2004) and measured SCRs. Despite their very poor performance on the cognitive task requiring the accurate identification of negative facial expressions, females with Turner syndrome showed normal acquisition of fear conditioning, indicating that in this respect they had normal amygdala function (LeDoux 2000). There is evidence from this experiment that amygdala-related cognitive performance could be impaired, in the presence of intact autonomic responsiveness to a threatening stimulus.…”
Section: X-linked Genes and The Modulation Of Amygdala Activationmentioning
confidence: 70%
“…AMYGDALA-CORTICAL FUNCTIONAL CONNECTIVITY AND PARANOIA Threatening or traumatic stimuli are probably processed in parallel by two distinct neural systems (Bechara et al 1995;LeDoux 2000). The subjective experience of fear relies upon amygdala-medial frontal activity (as well as autonomic arousal).…”
Section: Subcortical Processing Of Threatening Stimulimentioning
confidence: 99%
See 1 more Smart Citation